Lipoprotein(a), venous thromboembolism and COVID-19: A pilot study. (January 2022) - Nurmohamed, Nick S.; Collard, Didier; Reeskamp, Laurens F.; Kaiser, Yannick; Kroon, Jeffrey; Tromp, Tycho R.; van den Born, Bert-Jan H.; Coppens, Michiel; Vlaar, Alexander P.J.; Beudel, Martijn; van de Beek, Diederik; van Es, Nick; et al.
Abstract: Background and aims: Thrombosis is a major driver of adverse outcome and mortality in patients with Coronavirus disease 2019 (COVID-19). Hypercoagulability may be related to the cytokine storm associated with COVID-19, which is mainly driven by interleukin (IL)-6. Plasma lipoprotein(a) [Lp(a)] levels increase following IL-6 upregulation and Lp(a) has anti-fibrinolytic properties. This study investigated whether Lp(a) elevation may contribute to the pro-thrombotic state hallmarking COVID-19 patients. Methods: Lp(a), IL-6 and C-reactive protein (CRP) levels were measured in 219 hospitalized patients with COVID-19 and analyzed with linear mixed effects model. The baseline biomarkers and increases during admission were related to venous thromboembolism (VTE) incidence and clinical outcomes in a Kaplan-Meier and logistic regression analysis. Results: Lp(a) levels increased significantly by a mean of 16.9 mg/dl in patients with COVID-19 during the first 21 days after admission. Serial Lp(a) measurements were available in 146 patients. In the top tertile of Lp(a) increase, 56.2% of COVID-19 patients experienced a VTE event compared to 18.4% in the lowest tertile (RR 3.06, 95% CI 1.61–5.81; p  < 0.001). This association remained significant after adjusting for age, sex, IL-6 and CRP increase and number of measurements. Increases in IL-6 and CRP were not associated with VTE. Increase in Lp(a) was strongly correlated with increase in IL-6 (r = 0.44, 95% CI 0.30–0.56, p  < 0.001). Conclusions: Increases in Lp(a) levels during the acute phase of COVID-19 were strongly associated with VTE incidence. The acute increase in anti-fibrinolytic Lp(a) may tilt the balance to VTE in patients hospitalized for COVID-19. Graphical abstract: Image 1 Highlights: IL-6 increase leads to an increase in Lp(a) levels. Lp(a) levels increase during hospitalization for COVID-19. Increases in Lp(a) during hospitalization are associated with venous thromboembolism incidence up to 56%.